Bioinformatics Analysis Reveals Abundant Short Alpha-Helices as a Common Structural Feature of Oomycete RxLR Effector Proteins. - Wenwu Ye; Yang Wang; Yuanchao Wang (PLoS ONE, 2015)
RxLR effectors represent one of the largest and most diverse effector families in oomycete plant pathogens. These effectors have attracted enormous attention since they can be delivered inside the plant cell and manipulates host immunity. With the exceptions of a signal peptide and the following RxLR-dEER and C-terminal W/Y/L motifs identified from the sequences themselves, nearly no functional domains have been found. Recently, protein structures of several RxLRs were revealed to comprise alpha-helical bundle repeats. However, approximately half of all RxLRs lack obvious W/Y/L motifs, which are associated with helical structures. In this study, secondary structure prediction of the putative RxLR proteins was performed. We found that the C-terminus of the majority of these RxLR proteins, irrespective of the presence of W/Y/L motifs, contains abundant short alpha-helices. Since a large-scale experimental determination of protein structures has been difficult to date, results of the current study extend our understanding on the oomycete RxLR effectors in protein secondary structures from individual members to the entire family. Moreover, we identified less alpha-helix-rich proteins from secretomes of several oomycete and fungal organisms in which RxLRs have not been identified, providing additional evidence that these organisms are unlikely to harbor RxLR-like proteins. Therefore, these results provide additional information that will aid further studies on the evolution and functional mechanisms of RxLR effectors.